Magnetically active Ag–Zn nanoferrites synthesized by solution combustion route: physical chemical studies and density functional theory analysis. (December 2021) - Singh, J.; Kumar, D.; Kumar, P.S.; Huerta Aguilar, C.A.; Vo, D.-V.N.; Sharma, A.; Kaur, H.
Abstract: Nanoparticles with mixed compositions, particularly spinel ferrites with magnetic activity, have arisen as contrast agents for magnetic resonance imaging, magnetic hyperthermia. For such applications, it is desirable to possess specific particle size and physicochemical properties, i.e., magnetic response, porosity, crystallinity, and so on. It is well known that controlling specific variables in the synthetic process has a dramatic effect on final product properties and behavior. Amid preparation techniques reported in the literature, low-temperature solution combustion method has shown the ability to control and direct synthesis simply and efficiently. We are presenting a study about controlling and tuning the magnetic properties and the effect of particle size modified in Ag–Zn nanoferrites with different amounts of Co and Ni as doping metals. Different combinations of Co and Ni within Ag–Zn (Ag0.25 Zn0.5-x Mx Fe2.25 O4 ) nanoferrites have been synthesized using the low-temperature solution combustion technique, and this method proved to be efficient and reliable for developing homogenous, fine structured materials. X-ray diffraction confirmed that the atomic structure of prepared nanoferrites is pure and cubic, whereas electron microscopy confirmed a semispherical and monodisperse morphology with particle diameter around 20 nm. The magnetic behavior of bred materials has been explained by analyzing magnetic factors such as saturation magnetization, coercivity, and retentivity, and all experimental findings are matched with theoretical density functional theory (DFT) studies to understand the effect of each material within A and B sites in ferrite crystal cell. The observed magnetic properties highlight the superparamagnetic behavior and the effect of doping metals which is an asset in developing new materials for diagnostic and therapeutic applications. DFT modeling was achieved in an attempt to understand the effect of metal substitution in cubic ferrite cells. Graphical abstract: Image 1 Highlights: Co and Ni-doped Ag–Zn spinel nanoferrites were synthesized using low temperature solution combustion (LTSC) process. Mössbauer's spectroscopy confirmed that iron atoms existed in Fe 3+ oxidation state. Magnetic transitions were successfully discussed of Ag–Zn nanoferrites. Density functional theory study explains the effect of metal substitution in cubic ferrites.